The Warsaw Convention 1929: Limitation Of The Air Carrier Liability In Death And Personal Injury Of The Passenger - Othman, Mohd Bahrin bin (Journal of Malaysian and Comparative Law, 2001)
The maxim was "what the engineers are doing for machines, we must do for the law". The players were the ’think tank’ of the air industry. The result was the Warsaw Convention for the Unification of Certain Rules Relating to International carriage by Air (1929). For years it has been praised as the most successful unification of private law and has achieved almost universal application. However the limitation of air carrier liability, particularly in the death and personal injury of its passengers of which is the core of the liability system in the Warsaw Convention, he become the main target of criticism over the years.